Financial Visibility and the Decision to Go Private - Mehran, Hamid; Peristiani, Stavros (Review of Financial Studies, 2010)
[A large fraction of the companies that went private between 1990 and 2007 were fairly young public firms, often with the same management team making the crucial restructuring decisions at both the time of the initial public offering (IPO) and the buyout. This article investigates the determinants of the decision to go private over a firm's entire public life cycle. Our evidence reveals that firms with declining growth in analyst coverage, falling institutional ownership, and low stock turnover were more likely to go private and opted to do so sooner. We argue that a primary reason behind the decision of IPO firms to abandon their public listing was a failure to attract a critical mass of financial visibility and investor interest.]